Association between physical activity changes and incident myocardial infarction after ischemic stroke: a nationwide population-based study - Dae Young Cheon; Kyung do Han; Yeon Jung Lee; Jeen Hwa Lee; Myung Soo Park; Do Young Kim; Jae Hyuk Choi; Sook Jin Lee; Kyung-Ho Yu; Seongwoo Han; Sunki Lee; Minwoo Lee (BMC, 2024)
Abstract Background The impact of changes in physical activity after ischemic stroke (IS) on the subsequent myocardial infarction (MI) risk is not fully understood. We aimed to investigate the effects of changes in physical activity on the risk of MI after acute IS using data from the Korean National Health Insurance Services Database. Methods 224,764 patients newly diagnosed with IS between 2010 and 2016 who underwent two serial biannual health checkups were included. The participants were divided into four categories according to changes in their physical activity: persistent non-exercisers, new exercisers, exercise dropouts, and exercise maintainers. The primary outcome was a new diagnosis of incident MI. Multivariable Cox proportional models were used to assess the effects of changes in exercise habits on the risk of MI. Results After a median of 4.25 years of follow-up, 6,611 (2.94%) MI cases were observed. After adjusting for confounders, new exercisers and exercise maintainers were significantly associated with a lower risk of incident MI than persistent non-exercisers (aHR, 0.849; 95% CI, 0.792-0.911; P-value < 0.001; and aHR, 0.746; 95% CI, 0.696-0.801; P-value < 0.001, respectively). Effects were consistent across sexes, more pronounced in those > 65 years. Notably, any level of physical activity after stroke was associated with a reduced MI risk compared to no exercise. Conclusions In this nationwide cohort study, commencing or sustaining physical activity after an IS corresponded to a diminished likelihood of subsequent MI development. Advocating physical activity in ambulatory stroke survivors could potentially attenuate the prospective risk of MI.